Evaluating awareness towards ev: An exploratory study - Nooraini, Ismail; Osman, Nor Hasni; Mohd Zamani, Siti Norhasmaedayu (IJPUBLICATION, 2020)
A significant obstacle to the uptake of electric vehicles (EVs) is that consumers lack awareness and do not see them as viable options. A survey to analyze consumers' awareness of existing EVs was conducted toward existing EVs in Malaysia. The focus area is in Langkawi Island, where the place aims to be a low carbon Island by 2030. The understanding of the awareness of air pollution is essential to inform government approaches to addressing this issue. Thus, a comprehensive questionnaire survey has conducted with 506 respondents from Malaysian citizens. Data for this study comes from Malaysian citizens' over the period from August to September 2020 and conducting in Malay language.